Development and validation of an experimental life support system for assessing the effects of global climate change and environmental contamination on estuarine and coastal marine benthic communities. (29th May 2013) - Coelho, Francisco J. R. C.; Rocha, Rui J. M.; Pires, Ana C. C.; Ladeiro, Bruno; Castanheira, José M.; Costa, Rodrigo; Almeida, Adelaide; Cunha, Ângela; Lillebø, Ana Isabel; Ribeiro, Rui; Pereira, Ruth; Lopes, Isabel; et al.
Abstract: An experimental life support system (ELSS) was constructed to study the interactive effects of multiple stressors on coastal and estuarine benthic communities, specifically perturbations driven by global climate change and anthropogenic environmental contamination. The ELSS allows researchers to control salinity, pH, temperature, ultraviolet radiation (UVR), tidal rhythms and exposure to selected contaminants. Unlike most microcosms previously described, our system enables true independent replication (including randomization). In addition to this, it can be assembled using commercially available materials and equipment, thereby facilitating the replication of identical experimental setups in different geographical locations. Here, we validate the reproducibility and environmental quality of the system by comparing chemical and biological parameters recorded in our ELSS with those prevalent in the natural environment. Water, sediment microbial community and ragworm (the polychaete Hediste diversicolor ) samples were obtained from four microcosms after 57 days of operation. In general, average concentrations of dissolved inorganic nutrients (NO3 − ; NH4 + and PO4 −3 ) in the water column of the ELSS experimental control units were within the range of concentrations recorded in the natural environment. While some shifts in bacterial community composition were observed between in situ and ELSS sediment samples, the relative abundance of most metabolically active bacterial taxa appeared to be stable. In addition, ELSS operation did not significantly affect survival, oxidative stress and neurological biomarkers of the model organism Hediste diversicolor . The validation data indicate that this system can be used to assess independent or interactive effects of climate change and environmental contamination on benthic communities. Researchers will be able to simulate the effects of these stressors on processes driven by microbial communities, sediment and seawater chemistry and to evaluate potential consequences to sediment toxicity using model organisms such as Hediste diversicolor .